Modulation of Perturbed Cardiac Metabolism in Rats Under High-Altitude Hypoxia by Combination Treatment With L-carnitine and Trimetazidine - Xie, Hebing; Xu, Gang; Aa, Jiye; Gu, Shuhua; Gao, Yuqi (Frontiers in Physiology, 2021)
High-altitude hypoxia has long been recognized as a vital etiology for high altitude illnesses. High-altitude myocardial injury (HAMI) usually occurs in people who suffered from high-altitude exposure. Until now, the molecular mechanism of HAMI remains elusive, which seriously hinder the prevention and treatment of HAMI. L-carnitine and trimetazidine are classic cardiovascular protective medicines. Here, we employ metabolomic method, based on GC/MS, to explore the metabolites perturbation of rats exposed to high altitude, and then illustrate the metabolic pathways associated with the modulatory effect of L-carnitine combined with trimetazidine on rats with high altitude exposure. The results show that metabolites in the myocardium in rats under high-altitude hypoxia were markedly changed, such as branched-chain amino acids (BCAA, leucine, isoleucine and valine), taurine, succinic acid, fumaric acid, lactic acid, pyruvic acid, 3-hydroxybutyrate and DHA (Docosahexaenoic acid), while L-carnitine combined with trimetazidine modulated and improved the abnormal changes in energy substances caused by high-altitude hypoxia. L-carnitine mainly promoted the metabolism of fatty acids, while trimetazidine enhanced the glycolysis process. The combined administration of the two components not only increased the metabolism of fatty acids, but also promoted the aerobic glycolysis. Meanwhile, it contributed to the decrease in the elevation in some of TCA (tricarboxylic acid) cycle intermediates, decrease in the production of 3-hydroxybutanoic acid, and relief of the abnormal energy metabolism process in organisms and the cardiac tissue. Taken together, our analysis delineates the metabolites landscape of myocardial tissue after rats exposed to high altitude. Moreover, L-carnitine combined with trimetazidine can relieve the HAMI through modulated and improved the abnormal changes in energy substances caused by high-altitude hypoxia.